The Effectiveness of The Jigsaw-Type Cooperative Learning Model on the Mathematical Communication Ability of Grade X High School Students - Neta Deliana Bau; Aloisius Loka Son; Ferdinandus Mone (Indonesian Educational Research Journal, 2023)
This study was conducted with the aim of determining the effectiveness of the jigsaw-type cooperative learning model on students' mathematical communication ability. This research uses quantitative methods with a quasi-experimental approach. This research design uses a pretest-postest control group design. The participants of this study were grade X students of one of the high schools in North Central Timor Regency. This research was carried out in the even semester of the 2022/2023 academic year The research instrument was in the form of a mathematical communication ability test and observation sheets. The results of this study show that jigsaw-type cooperative learning is effective in improving students' mathematical communication ability. this is illustrated by the results of research that shows that the achievement and improvement of mathematical communication ability of students who learn through the jigsaw-type cooperative learning model is better than students who learn through conventional models